(untitled) (Global Journal of Science Frontier Research, 2017)
Developed and analyzed two-barrier structures -silicon-based photo detectors with high sensitivity in the field of integrated short-range. Developed silicon-based photo detector with high sensitivity integrated in the short range. The effect of gamma radiation on the mechanism of current transport in the structure type Schottky barrier, and in the p-n junctions. It is shown that the double-barrier structure can improve the photovoltaic parameters of conventional detectors. We studied the effect of gamma radiation on the origin of the current mechanism in the structure as a whole, and in the Schottky barrier in the p -n -transitions separately. Also studied the effect of radiation on the photoelectric and photoluminescence parameters of the two barrier structure. Shown that two barrier structures can improve the photoelectric parameters of conventional detectors.